Elasticity Modification of Biomaterials Used in 3D Printing with an Elastin–Silk-like Recombinant Protein - Violetta Cecuda-Adamczewska; Agnieszka Romanik-Chruścielewska; Katarzyna Kosowska; Iwona Sokołowska; Natalia Łukasiewicz; Paulina Korycka; Katarzyna Florys-Jankowska; Agnieszka Zakrzewska; Michał Wszoła; Marta Klak (Journal of Functional Biomaterials, 2024)
The recombinant structural protein described in this study was designed based on sequences derived from elastin and silk. Silk–elastin hybrid copolymers are characterized by high solubility while maintaining high product flexibility. The phase transition temperature from aqueous solution to hydrogel, as well as other physicochemical and mechanical properties of such particles, can differ significantly depending on the number of sequence repeats. We present a preliminary characterization of the EJ17zipR protein obtained in high yield in a prokaryotic expression system and efficiently purified via a multistep process. Its addition significantly improves biomaterial’s rheological and mechanical properties, especially elasticity. As a result, EJ17zipR appears to be a promising component for bioinks designed to print spatially complex structures that positively influence both shape retention and the internal transport of body fluids. The results of biological studies indicate that the addition of the studied protein creates a favorable microenvironment for cell adhesion, growth, and migration.